Method for improving degradation resistance of phosphate fire-resistant oil

Through the combined treatment of catalytic oxidation and adsorbent, the problem of difficult removal of unstable components such as phenols in fuel oil in phosphate is solved, which significantly improves its anti-degradation performance and stability, and improves the long-term operation safety of the hydraulic system.

CN119285670APending Publication Date: 2025-01-10XIAN THERMAL POWER RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417808.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove phenolics and other unstable components remaining in fuel-resistant oil in the prior art, resulting in insufficient anti-degradation performance and affecting the long-term and stable operation of the hydraulic system.

Method used

The catalytic oxidation reaction is carried out using an oxidizing agent and a catalyst to thoroughly oxidize unstable phenols and other easily oxidized substances, and then use adsorbents to remove the oxidation product to improve the resistance of phosphate fuel resistance to deterioration.

Benefits of technology

After deep treatment, the content and acid value of the phenolic components are significantly reduced, the oxidative stability and resistivity of the oil are improved, and the comprehensive use performance of phosphate esters with fuel resistance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285670A_ABST
    Figure CN119285670A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of degradation resistance of phosphate fire-resistant oil, and relates to a method for improving the degradation resistance of the phosphate fire-resistant oil, which specifically comprises the following steps: putting a catalyst into the phosphate fire-resistant oil, introducing oxygen, heating and stirring to carry out catalytic oxidation reaction, so that unstable phenols and other easily oxidized substances are thoroughly oxidized; after thorough oxidation, the catalyst is completely filtered, an adsorbent is added, and after oxidation products are removed by the adsorbent, the phosphate fire-resistant oil with improved degradation resistance is obtained; according to the method, an oxidation method and an adsorption method are combined to carry out advanced treatment on the phosphate fire-resistant oil, the content of easily degraded components such as residual phenols after treatment is obviously reduced, the method is easy to operate and good in treatment effect, and the method plays an important role in promoting development of a phosphate fire-resistant oil production technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fire-resistant oil deterioration resistance, and relates to a method for improving the deterioration resistance of phosphate fire-resistant oil. Background Art

[0002] In key industries such as electricity, aviation, and metallurgy, phosphate fire-resistant oil plays a vital role as the working medium of hydraulic systems with its excellent flame retardant properties and stability. Especially in the regulating system of generator sets, its performance directly affects the safe operation, efficiency, and economic benefits of the units. Phosphate fire-resistant oils, especially fully synthetic oils based on triaryl phosphate (TAP), such as tri(dimethylphenyl) phosphate (TXP), tri(isopropylphenyl) phosphate (IPPP), and di(tert-butylphenyl) phenyl phosphate (DBPP), are highly favored due to their unique chemical structure. Among them, TXP has become one of the most widely used raw materials in the field of phosphate fire-resistant oils due to its stable chemical properties and excellent performance.

[0003] However, despite the excellent performance of TXP, the difficulties faced in its production process cannot be ignored. Specifically, due to the purity limit of synthetic raw materials and the limitations of the purification process, it is often difficult to completely remove trace amounts of phenols and other components that are easily oxidized and deteriorated in TXP. These residues are easily affected by oxygen, moisture or metal ions during subsequent use, and undergo oxidation or catalytic reactions, resulting in gradual deterioration of oil performance. Oxidation stability is an important indicator for measuring the ability of phosphate ester fire-resistant oils to resist degradation. A reduction in its level will directly threaten the long-term stable operation of the hydraulic system.

[0004] At present, although there are many adsorbents on the market for improving the purity of phosphate fire-resistant oils, these adsorbents are still inefficient in removing unstable components such as phenols, and it is difficult to meet the increasingly stringent industrial application requirements. Therefore, how to effectively remove residual phenols and other unstable components in TXP to improve the overall anti-degradation performance of phosphate fire-resistant oils has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present invention is to provide a method for improving the degradation resistance of phosphate fire-resistant oil, by using an oxidant and a catalyst to completely oxidize unstable phenols and other easily oxidizable substances, and then removing the oxidation products through an adsorbent, thereby greatly improving the degradation resistance of phosphate fire-resistant oil.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for improving the degradation resistance of phosphate ester fire-resistant oil, which specifically comprises the following steps:

[0008] The catalyst is placed in the phosphate fire-resistant oil, oxygen is introduced, and the mixture is heated and stirred to perform a catalytic oxidation reaction, so that unstable phenols and other easily oxidizable substances are completely oxidized;

[0009] After thorough oxidation, the catalyst is completely filtered, and an adsorbent is added. After the adsorbent removes the oxidation product, a phosphate fire-resistant oil with improved anti-degradation capability is obtained.

[0010] Preferably, the phosphate fire-resistant oil is triaryl phosphate (TXP) with tris(dimethylphenyl) phosphate as the main component.

[0011] Preferably, the catalyst is metal copper powder, chromium trioxide or vanadium pentoxide, and the purity of each of them is greater than 99.0%.

[0012] Preferably, the temperature of the oxidation reaction is 60° C. to 100° C.; and the time of the oxidation reaction is 4 h to 8 h.

[0013] Preferably, the amount of the catalyst is 0.3% to 0.5% of the mass of the phosphate fire-resistant oil.

[0014] Preferably, the oxygen flow rate is 100 mL / min to 200 mL / min, and the oxygen purity is greater than 99.0%.

[0015] Preferably, the adsorbent is a silica-alumina-based polar adsorbent or a combination of a silica-alumina-based polar adsorbent and an activated aluminum-based oxide adsorbent, and the mass percentage of the silica-alumina-based polar adsorbent in the composition is greater than 85%.

[0016] Preferably, the mass of the adsorbent is 4% to 6% of the mass of the phosphate fire-resistant oil.

[0017] Preferably, the adsorbent needs to be dried at 160° C. for 2 h before use and cooled to room temperature for standby use.

[0018] Preferably, the adsorption temperature is 60°C to 70°C; and the adsorption time is 2h to 3h.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts "oxidation method" combined with "adsorption method" to deeply treat TXP, and uses oxidants and catalysts to oxidize unstable phenols and other easily oxidizable substances, and then uses adsorbents to remove oxidation products. The types and contents of components such as phenols in the deeply treated TXP are significantly reduced, and components that are easily degraded are effectively removed. The method is simple to operate and has good treatment effect. While improving the oxidation stability of phosphate fire-resistant oil, it can also further reduce its acid value and increase its resistivity. The comprehensive use performance of phosphate fire-resistant oil can be effectively improved, which can provide certain technical support for the development and production of domestic phosphate fire-resistant oil, and play an important role in promoting the development of phosphate fire-resistant oil production technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The gas chromatogram of the treated phosphate fire-resistant oil obtained in Example 1;

[0022] Figure 2 This is a comparison chart of the acid values ​​of the phosphate fire-resistant oil before and after treatment during aging obtained in Example 1;

[0023] Figure 3 This is a comparison chart of the resistivity of the phosphate fire-resistant oil before and after treatment during aging obtained in Example 1. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0026] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0027] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0028] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0029] In the production process of TXP, due to the limitations of the purity of synthetic raw materials and purification processes, a small amount of phenols and other components that are easily oxidized and deteriorated are difficult to be separated, and the existing adsorbents have limited removal capacity for them, resulting in the key anti-deterioration performance indicators of TXP, such as oxidation stability, often being at a low level. In order to reduce the content of easily oxidized and deteriorated components in TXP as much as possible, the present invention uses "oxidation method" combined with "adsorption method" for deep treatment, that is, using suitable catalysts and oxidation conditions to moderately oxidize such unstable components that are difficult to separate, and then using adsorbents to adsorb and remove the oxidized products.

[0030] The present invention provides a method for improving the degradation resistance of phosphate ester fire-resistant oil, which specifically comprises the following steps:

[0031] The catalyst is placed in the phosphate fire-resistant oil, oxygen is introduced, and the mixture is heated and stirred to perform a catalytic oxidation reaction, so that unstable phenols and other easily oxidizable substances are completely oxidized;

[0032] After thorough oxidation, the catalyst is completely filtered, and an adsorbent is added. After the adsorbent removes the oxidation product, a phosphate fire-resistant oil with improved anti-degradation capability is obtained.

[0033] The phosphate fire-resistant oil is a triaryl phosphate with tris(dimethylphenyl) phosphate as a main component.

[0034] The catalyst is metal copper powder (with a particle size of 150-200 meshes), chromium trioxide (Cr2O3) or vanadium pentoxide (V2O5), and the purity of the metal copper powder, chromium trioxide or vanadium pentoxide selected as the catalyst has high catalytic activity and can effectively promote the oxidation reaction of unstable phenols and other substances in phosphate fire-resistant oil at a relatively low temperature. By using an oxidant and a catalyst, the unstable phenols and other easily oxidizable substances are oxidized, thereby accelerating their conversion into more stable compounds.

[0035] The temperature of the oxidation reaction is 60°C to 100°C; the time of the oxidation reaction is 4h to 8h; the amount of the catalyst is 0.3% to 0.5% of the mass of the phosphate fire-resistant oil; the oxygen flow rate is 100mL / min to 200mL / min, and the oxygen purity is greater than 99.0%.

[0036] The adsorbent is a silica-aluminum-based polar adsorbent or a combination of a silica-aluminum-based polar adsorbent and an activated aluminum-based oxide adsorbent, and the mass percentage of the silica-aluminum-based polar adsorbent in the composition is greater than 85%; the selected silica-aluminum-based polar adsorbent or the combination of a silica-aluminum-based polar adsorbent and an activated aluminum-based oxide adsorbent has good adsorption performance for oxidation products such as aldehydes, ketones, etc., and can efficiently remove these impurities. The adsorption treatment further purifies the phosphate fire-resistant oil, removes the by-products produced by the oxidation reaction, and improves the purity and anti-deterioration performance of the oil.

[0037] The mass of the adsorbent is 4% to 6% of the mass of the phosphate fire-resistant oil; the adsorbent needs to be dried at 160° C. for 2 hours before use and cooled to room temperature for standby use; the adsorption temperature is 60° C. to 70° C.; and the adsorption time is 2h to 3h.

[0038] Example 1

[0039] Metal copper powder with a purity of 99.5% and a particle size of 200 mesh was selected as a catalyst, and JX-001 silicon-aluminum adsorbent was used as an adsorbent for moderately degraded products to improve the performance of TXP produced by Manufacturer A.

[0040] Add 0.9 g of metallic copper powder to 300 g of TXP, introduce oxygen with a purity of 99.9% and a flow rate of 200 mL / min, and carry out catalytic oxidation reaction at 60°C for 4 hours. Filter the metallic copper powder completely with qualitative filter paper, and place the oxidized TXP in a constant temperature bath at 60°C for standby use.

[0041] The JX-001 silicon-aluminum-based polar adsorbent was dried at 160°C for 2 hours and cooled to room temperature, and 12.0 g of the JX-001 silicon-aluminum-based polar adsorbent was added to the oxidized TXP. The oxidized TXP was kept at a constant temperature of 60°C and stirred at 800 r / min for 2 hours. After the adsorption was completed, it was filtered with a qualitative filter paper, and the filtered TXP was collected to obtain a phosphate fire-resistant oil with improved anti-deterioration performance.

[0042] The key index detection and analysis of Plant A before and after TXP treatment are shown in Table 1.

[0043] Table 1 Analysis results of key indicators before and after TXP treatment in Plant A

[0044]

[0045]

[0046] Example 2

[0047] Cr2O3 with a purity of 99.1% was selected as the catalyst, and GT-150 silicon-aluminum adsorbent was used as the adsorbent for moderately degraded products, and the performance of TXP produced by manufacturer B was improved.

[0048] Add 1.2g Cr2O3 to 300g TXP, introduce oxygen with a purity of 99.5% and a flow rate of 150mL / min, and carry out catalytic oxidation reaction at 70℃ for 6h. Filter the Cr2O3 completely with qualitative filter paper, and place the oxidized TXP in a constant temperature bath at 65℃ for standby use.

[0049] The GT-150 silicon-aluminum-based polar adsorbent was dried at 160°C for 2 hours and cooled to room temperature, and 15.0 g of the GT-150 silicon-aluminum-based polar adsorbent was added to the oxidized TXP. The oxidized TXP was kept at a constant temperature of 65°C and stirred at 800 r / min for 2.5 hours. After the adsorption was completed, it was filtered with a qualitative filter paper, and the filtered TXP was collected to obtain a phosphate fire-resistant oil with improved anti-degradation performance.

[0050] The key index detection and analysis of Plant B before and after TXP treatment are shown in Table 2.

[0051] Table 2 Analysis results of key indicators before and after TXP treatment in Plant B

[0052]

[0053] Example 3

[0054] V2O5 with a purity of 99.6% was selected as the catalyst, and LM-200 silicon-aluminum adsorbent and AT-100 activated alumina were compounded as the adsorbent for moderate degradation products, where the mass fraction of LM-200 silicon-aluminum adsorbent was 90%, and the performance of TXP produced by manufacturer C was improved.

[0055] Add 1.5g V2O5 to 300g TXP, introduce oxygen with a purity of 99.8% and a flow rate of 100mL / min, and carry out catalytic oxidation reaction at 90℃ for 4h. Filter the V2O5 completely with qualitative filter paper, and place the oxidized TXP in a constant temperature bath at 70℃ for standby use.

[0056] The LM-200 silicon-aluminum adsorbent and AT-100 activated alumina were dried at 160°C for 2 hours and cooled to room temperature. 16.2g LM-200 silicon-aluminum adsorbent and 1.8g AT-100 activated alumina were added to the oxidized TXP. The oxidized TXP was kept at a constant temperature of 70°C and stirred at 800r / min for 3 hours. After the adsorption was completed, it was filtered with qualitative filter paper and the filtered TXP was collected. The TXP with improved anti-deterioration performance was phosphate fire-resistant oil.

[0057] The key index detection and analysis of Plant C before and after TXP treatment are shown in Table 3.

[0058] Table 3 Analysis results of key indicators before and after TXP treatment in Plant C

[0059]

[0060] Example 4

[0061] Metal copper powder with a purity of 99.5% and a particle size of 150 mesh was selected as the catalyst, and LM-200 silicon-aluminum adsorbent compounded with AT-100 activated alumina was used as the adsorbent for moderate degradation products, in which the mass fraction of LM-200 silicon-aluminum adsorbent was 85.1%. The performance of TXP produced by manufacturer D was improved.

[0062] Add 1.5 g of metallic copper powder to 300 g of TXP, introduce oxygen with a purity of 99.1% and a flow rate of 150 mL / min, and carry out catalytic oxidation reaction at 100°C for 4 hours. Filter the metallic copper powder completely with qualitative filter paper, and place the oxidized TXP in a constant temperature bath at 70°C for standby use.

[0063] The LM-200 silicon-aluminum adsorbent and AT-100 activated alumina were dried at 160°C for 2 hours and cooled to room temperature. 16.2g LM-200 silicon-aluminum adsorbent and 1.8g AT-100 activated alumina were added to the oxidized TXP. The oxidized TXP was kept at a constant temperature of 70°C and stirred at 800r / min for 3 hours. After the adsorption was completed, it was filtered with qualitative filter paper and the filtered TXP was collected. The TXP with improved anti-deterioration performance was phosphate fire-resistant oil.

[0064] Example 5

[0065] V2O5 with a purity of 99.6% was selected as the catalyst, and LM-200 silicon-aluminum adsorbent and AT-100 activated alumina were compounded as the adsorbent for moderate degradation products, where the mass fraction of LM-200 silicon-aluminum adsorbent was 90%, and the performance of TXP produced by manufacturer C was improved.

[0066] Add 1.5g V2O5 to 300g TXP, introduce oxygen with a purity of 99.8% and a flow rate of 100mL / min, and carry out catalytic oxidation reaction at 60°C for 8h. Filter the metallic copper powder completely with qualitative filter paper, and place the oxidized TXP in a constant temperature bath at 70°C for standby use.

[0067] The LM-200 silicon-aluminum adsorbent and AT-100 activated alumina were dried at 160°C for 2 hours and cooled to room temperature. 16.2g LM-200 silicon-aluminum adsorbent and 1.8g AT-100 activated alumina were added to the oxidized TXP. The oxidized TXP was kept at a constant temperature of 70°C and stirred at 800r / min for 3 hours. After the adsorption was completed, it was filtered with qualitative filter paper and the filtered TXP was collected. The TXP with improved anti-deterioration performance was phosphate fire-resistant oil.

[0068] Among them, DL / T 429.2-2016 is the "Determination of Color of Oil for Power Use"; GB / T 264-1983 is the "Determination of Acid Value of Petroleum Products"; DL / T 421-2009 is the "Determination of Volume Resistivity of Oil for Power Use"; SH / T0308-1992 is the "Determination of Air Release Value of Lubricating Oil"; EN14833:2005 is the "Determination of Hydrolysis Stability of Phosphate Ester Fire-Resistant Oils of Petroleum and Related Products"; EN14832:2005 is the "Determination of Oxidative Stability and Corrosion of Phosphate Ester Fire-Resistant Oils of Petroleum and Related Products".

[0069] From the treatment effects in Tables 1 to 3, it can be seen that after TXP is treated by the "oxidation method" combined with the "polar adsorption method", the oxidation stability of TXP is greatly improved, and key indicators such as acid value and resistivity are also greatly improved. For example, when the catalyst is a metal copper powder with a purity of 99.5%, the catalyst dosage is 0.3wt% TXP, the oxidation temperature is 60℃, the oxidation time is 4h, and the adsorbent is a JX-001 silicon-aluminum-based polar adsorbent, the acid value of TXP produced by Plant A can be reduced from 0.035mgKOH / g to 0.009mgKOH / g after moderate oxidation and adsorption regeneration treatment, and the resistivity can be reduced from 2.2×10 10 Ω·cm increased to 3.3×10 11 In particular, the oxidation stability acid value index of TXP from Plant A dropped from 0.48 mgKOH / g before treatment to 0.20 mgKOH / g, indicating that a small amount of phenols and other easily deteriorated components in TXP have been basically removed, and the anti-deterioration ability has been effectively improved.

[0070] In order to verify the effect of "oxidation method" combined with "polar adsorption method" on the removal of a small amount of phenols and other easily deteriorated substances remaining in TXP, gas chromatography analysis and testing were carried out on the TXP of Plant A before and after treatment. The results are as follows: Figure 1 shown.

[0071] Depend on Figure 1It can be seen that the sample has peaks at retention times of 3.458min and 3.652min. After comparison with the chromatographic peak of the dimethylphenol standard, the compounds corresponding to the peaks of the sample at the above retention times are 3,5-dimethylphenol and 3,4-dimethylphenol. According to the chromatographic peak area, the content of 3,5-dimethylphenol in the base oil sample is reduced to 0.019%, the content of 3,4-dimethylphenol is reduced to 0.004%, and no compounds such as 2,4-dimethylphenol, 2,5-dimethylphenol and 2,3-dimethylphenol are detected. The total content of dimethylphenol in the sample is reduced from 0.281% before treatment to 0.023%, indicating that the easily oxidized components are effectively removed. The types and contents of phenolic substances in TXP of Plant A before and after treatment are shown in Table 4.

[0072] Table 4 Comparison of types and contents of phenolic substances in TXP of plant A before and after oxidation treatment

[0073]

[0074]

[0075] In order to further verify the anti-degradation performance of the treated TXP, the treated TXP of Plant A was subjected to a closed cup aging test according to the requirements of DL / T1705-2017 "Closed Cup Aging Test Method for Phosphate Ester Fire-Resistant Oils". During the aging period, the changes in the acid value and resistivity of the samples were tracked to evaluate the anti-degradation performance of the samples. Figure 2 and Figure 3 This is a graph showing the trend of TXP acid value and resistivity changes before and after treatment during the aging test.

[0076] Depend on Figure 2 and Figure 3 It can be seen that with the extension of aging time, the acid value and volume resistivity of TXP before and after treatment show different degrees of deterioration. Among them, the acid value of TXP before treatment reaches 0.15 mg KOH / g on the 20th day, and the acid value of TXP after treatment reaches 0.15 mg KOH / g on the 30th day; the resistivity of TXP before treatment reaches 5.9×10 9 Ω·cm, the resistivity of TXP after treatment reached 5.9×10 9 The acid value and volume resistivity of TXP before treatment deteriorate significantly faster than those after treatment, indicating that the anti-deterioration performance of TXP before treatment is significantly better than that of TXP before treatment.

[0077] In order to verify the effect of the method of the present invention on the comprehensive performance of TXP, the treated TXP of Plant A was fully analyzed and tested according to the standard requirements of new oil in DL / T571-2014 "Guidelines for Operation and Maintenance of Phosphate Fire-Resistant Oil for Power Plants", and the test results are shown in Table 5.

[0078] Table 5 Performance test results of TXP samples after treatment in Example 1

[0079]

[0080]

[0081] It can be seen from Table 5 that after TXP is treated by the method of the present invention, its key indicators such as oxidation stability, acid value and resistivity are effectively improved, while other basic indicators of oil products such as kinematic viscosity, pour point and autoignition point are not affected, indicating that the comprehensive performance of the oil product is effectively improved.

[0082] TXP was selectively oxidized by combining the "oxidation method" with the "polar adsorption method" to oxidize unstable phenols and other easily oxidizable substances, and then the oxidation products were removed by polar adsorbents. The gas chromatography test results showed that after deep treatment, the types and contents of easily degradable components such as phenols in TXP were significantly reduced, and the easily degradable components were removed after treatment.

[0083] The results of closed cup aging test and full analysis test of treated TXP showed that key indicators such as acid value and volume resistivity of treated TXP were improved compared with those of untreated TXP, especially the oxidation stability was greatly improved. The comprehensive performance and anti-aging ability of treated TXP were significantly better than those of untreated TXP.

[0084] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for improving the degradation resistance of phosphate ester fire-resistant oil, characterized in that: The specific steps include: The catalyst is placed in the phosphate fire-resistant oil, oxygen is introduced, and the mixture is heated and stirred to perform a catalytic oxidation reaction, so that unstable phenols and other easily oxidizable substances are completely oxidized; After thorough oxidation, the catalyst is completely filtered, and an adsorbent is added. After the adsorbent removes the oxidation product, a phosphate fire-resistant oil with improved anti-degradation capability is obtained.

2. A method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The phosphate fire-resistant oil is a triaryl phosphate with tris dimethylphenyl phosphate as a main component.

3. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The catalyst is metal copper powder, chromium trioxide or vanadium pentoxide, and the purity of the catalyst is greater than 99.0%.

4. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The temperature of the oxidation reaction is 60° C. to 100° C.; the time of the oxidation reaction is 4 h to 8 h.

5. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The amount of the catalyst used is 0.3% to 0.5% of the mass of the phosphate fire-resistant oil.

6. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The oxygen flow rate is 100 mL / min to 200 mL / min, and the oxygen purity is greater than 99.0%.

7. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The adsorbent is a silicon-aluminum-based polar adsorbent or a combination of a silicon-aluminum-based polar adsorbent and an active aluminum-based oxide adsorbent, and the mass fraction of the silicon-aluminum-based polar adsorbent in the composition is greater than 85%.

8. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The mass of the adsorbent is 4% to 6% of the mass of the phosphate fire-resistant oil.

9. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The adsorbent must be dried at 160°C for 2 hours before use and cooled to room temperature for later use.

10. The method for improving the degradation resistance of phosphate ester fire-resistant oil according to claim 1, characterized in that: The adsorption temperature is 60° C. to 70° C.; the adsorption time is 2 h to 3 h.